Are Metaphyseal Sleeves a Viable Option to Treat Bone Defect during Revision Total Knee Arthroplasty? A Systematic Review - Bonanzinga, Tommaso; Akkawi, Ibrahim; Zahar, Akos; Gehrke, Thorsten; Haasper, Carl; Marcacci, Maurilio (Joints, 2019)
Purpose Bone loss is a challenging problem during revision total knee arthroplasty (TKA). Several studies have been published on the use of metaphyseal sleeves during revision TKA. Therefore, the aim of this systematic review was to summarize the clinical and radiographic outcomes of the use of metaphyseal sleeves in the setting of revision TKA.Methods A comprehensive search of PubMed, MEDLINE, CINAHL, Cochrane, EMBASE, and Google Scholar was performed, covering the period between January 1, 2000, and August 12, 2017. Various combinations of the following key words were used: “metaphyseal,” “sleeves,” “knee,” and “revision.” A total of 10 studies were included in the present systematic review.Results A total of 904 patients with 928 implants were recorded with a mean age of 69 years. They were evaluated at a mean follow-up of 45 months. Overall 1,413 sleeves, 888 in the tibia and 525 in the femur, were implanted. There were 36 septic re-revisions of the prosthetic components (4%). Five sleeves were found loose during septic re-revision; therefore, the rate of septic loosening of the sleeves was 0.35%. An aseptic re-revision of the prosthetic components was performed 27 times (3%). Ten sleeves were found loose during aseptic re-revision; therefore, the rate of aseptic loosening of the sleeves was 0.7%. Intraoperative fractures occurred 44 times (3.1%). Finally, clinical outcome was improved at final follow-up.Conclusion Metaphyseal sleeves demonstrate high radiographic signs of osteointegration, low septic loosening rate, low intraoperative fractures rate, and a good-to-excellent clinical outcome. Hence, they are a valid option to treat large metaphyseal bone defect during revision TKA.Level of Evidence This is a systematic review of level IV studies.
Keywords: revision total knee arthroplasty; metaphyseal sleeves; AORI; bone defect